The Autonomy of the Family as an Obstacle in Preventing and Identifying Assault of Children - Kerstin Nordlöf (Jesuit University Ignatianum in Krakow, 2017)
RESEARCH OBJECTIVE: The purpose of this article is to investigate whether the protection of the child has been considered sufficiently compared with the interests of the autonomy of the family within Swedish legislation. THE RESEARCH PROBLEM AND METHODS: The autonomy of the family is well protected by the European Convention for the Protection of Human Rights and Fundamental Freedoms in Article 8, where the right to family life is stipulated. But the article also authorises the right of a public authority to interfere in family life in accordance with the law for the prevention of crime. One reason for such interference could be the suspicion of domestic violence, which for centuries was considered to be a private concern. Article 3 of the Convention also forbids exposing a person to torture, inhuman or degrading treatment or punishment. The rights of the family are also expressed in the Convention on the Rights of the Child (Article 16), but more specifically in its view of the child. In the case of domestic violence, the Convention in Article 19 clarifies the responsibility of signatory states to protect the child from all kinds of assault by measures such as prevention and identification. THE PROCESS OF ARGUMENTATION: Due to the fact that domestic violence exists to such an extent that it severely affects society in different ways, Swedish legislation has been modified on several occasions. RESEARCH RESULTS: Even if the aim of those changes has been to uphold the autonomy of the family while preventing and identifying assaults within the family - particularly where children are involved - the question remains whether the protection of the child has been considered sufficiently compared with the interests of the autonomy of the family. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: In order to guarantee children a childhood and adolescence consisting of care, security and a good upbringing, further improvements - particularly within the Penal Code (1962:700) - are necessary to prevent and identify domestic violence against children.